Anti-ARHGAP26 Autoantibodies Are Associated With Isolated Cognitive Impairment - Bartels, Frederik; Prüss, Harald; Finke, Carsten (Frontiers in Neurology, 2018)
Autoantibodies against the RhoGTPase-activating protein 26 (ARHGAP26) were originally identified in the context of subacute autoimmune cerebellar ataxia. Further studies identified a wider clinical spectrum including psychotic, affective, and cognitive symptoms. Only a few patients reported so far had evidence of a tumor association. A prospective analysis between January 2015 and December 2017 at the Dept. of Neurology at Charité – Universitätsmedizin Berlin identified 14 patients with ARHGAP26 autoantibodies on a cell-based assay, of which three patients had additional brain immunohistochemistry staining of cerebellar molecular layer and Purkinje cells, who were therefore considered antibody-positive. In all three patients, ARHGAP26 autoantibodies were associated with tumors. In two patients, an isolated cognitive impairment without additional neurological deficits was observed. These cases thus further extend the clinical spectrum associated with ARHGAP26 autoantibodies and strengthen a potential paraneoplastic context.